Defining the Learning Curve of Anterior Total Hip Arthroplasty After Fellowship-specific Training. Issue 1 (1st January 2022) - Burnham, Robert R.; Kiernan, Hayley; Ortega, Liam F.; Wesolowski, Michael; Tauchen, Alexander; Russo, Matthew; Gerscovich, Daniel; Brown, Nicholas M.
Abstract : Purpose: To investigate the learning curve associated with performing direct anterior total hip arthroplasty (THA) immediately after fellowship training in this approach. Methods: This was a multicenter, retrospective study that collected data on all direct anterior THAs performed by four fellowship-trained arthroplasty surgeons in their first year of practice. Demographic data, surgical time, blood loss, surgical complications, and medical complications were recorded. Regression models were created to evaluate the outcomes of interest. A generalized linear mixed model was used to estimate the effect of the number of THA procedures performed, a proxy for surgical experience with this procedure, on the variables of interest. Results: A total of 286 patients undergoing direct anterior THA were included in this study. A decrease in surgical complications after approximately 40 cases and a decrease in medical complications at 25 to 50 cases were observed. Both surgical time and blood loss showed no learning curve. Conclusion: Extensive training with a direct anterior approach during fellowship minimizes the learning curve for blood loss and surgical time, but it continues to exist regarding perioperative surgical and medical complications. Recent fellowship graduates should be cautious and expect a learning curve of around 40 cases before complication rates begin to normalize.